PENGARUH DIVIDEND YIELD, PRICE EARNINGS RATIO DAN DEBT TO EQUITY RATIO TERHADAP RETURN SAHAM DENGAN INVESTMENT OPPORTUNITY SET SEBAGAI VARIABEL MODERATING - Hermi; Repal Sianipar (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2011)
This research is performed to examine the influence of variables Dividend Yield (D1), Price Earnings Ratio (PER) and the Debt to Equity Ratio (DER) to Stock Return, with the Investment Opportunity Set as moderating variables, in manufacturing companies listing on the Indonesia Stock Exchange period 2005 -2009.The population of this research is 134 companies the period 2005-2009. Sampling technique used was purposive sampling with the following criteria: (1) companies listed on the Indonesia Stock Exchange during the 2005-2009 period, (2) the company paying the dividends consistently for 5 consecutive years from 2005-2009. Data obtained from the publication of corporate financial statements included in the sampling criteria. Obtained the sample by 10 firms so that the number of observations in this study as many as 50. Analytical techniques used is moderated reggresion analysis.The results of this study indicate that partially, variabel of Price Earnings Ratio has a significant effect on the Stock Return with Investment Opportunity Set as moderating variable, while variables of Dividend Yield and Debt to Equity Ratio had no significant effect on stock return with Investment Opportunity Set as moderating variables. The Variables of Dividend Yield, Price Earnings Ratio and Debt to Equity Ratio simultaneously had no significant influence on stock Return with Investment Opportunity Set as moderating variable.